Patients’ perceptions and understanding of preoperative informed consent: A qualitative thematic analysis from Tanzania - Steven Michael; Willbroad Kyejo; Allyzain Ismail; Sunil Samji; Eric Aghan; Columba Mbekenga; Athar Ali (SAGE Open Medicine)
Background: Informed consent, grounded in the ethical principle of autonomy, represents a patient’s agreement to undergo a procedure. Given its critical role in protecting human rights and autonomy, obtaining informed consent before any surgery or procedure is now a mandatory practice. However, many studies question whether informed consent is conducted genuinely, ensuring proper understanding of the information disclosed, or merely serves as a medicolegal formality. This has led to increased malpractice, misunderstanding, anxiety, and overall postoperative dissatisfaction. Objective: This study aimed to explore patients’ perceptions and experiences regarding the informed consent process for elective surgeries, identifying key challenges and areas for improvement. Methods: This descriptive qualitative study was conducted at Aga Khan Hospital using individual in-depth interviews. Fourteen patients who had undergone elective surgery were recruited. Baseline data were presented in tables, and inductive thematic analysis was used to interpret the qualitative data. Results: Seven themes emerged from the data: Consent as a legal formality, autonomy, and decision-making, insufficient information, time constraints and lack of opportunities for questions, use of medical jargon, patients’ desired information, and overall satisfaction with care. Despite patients’ higher levels of education and the hospital’s patient-centered care approach, many felt the information provided was insufficient, superficial, and difficult to understand. Conclusion: The study found a significant gap between the information patients desired and what was provided. Insufficient information, coupled with the use of medical jargon and time constraints, adversely affected the informed consent process. Enhancing clarity in communication and allowing adequate time for discussions could improve patient understanding and satisfaction.